Development And Characterization Of Aripipraziole Loaded Solid Lipid Microparticles (Journal of Pharmaceutical Negative Results, 2023)
The major challenge for brain targeting is to cross the blood-brain barrier (BBB) which limits several drugs and molecules to penetrate into the brain. In our research, we developed aripiprazole encapsulated solid lipid microparticles and characterized them according to standard methods. Microparticles were prepared by a hot melts microencapsulation approach byapplying various concentrations ration of Span 20, Span 80, Tween 20, and Tween 80. The drug release mechanism has been shown for every optimized formulation.